Identifikasi Kecenderungan Pola Iklim Ekstrim di Pangkalpinang - Yuliarti, Aflah; Simanjuntak, Presli Panusunan; Ardiani, Normi (Seminar Nasional Lahan Suboptimal, 2023)
Yuliarti, A., Simanjuntak, P. P., & Ardiani, N. (2023). Identifying trends in extreme climate patterns in Pangkalpinang. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 417-427). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Human activities have led to an increase in global temperatures. This also increases the frequency of extreme climates such as extreme rainfall and air temperatures. Pangkalpinang City is the capital of the Bangka Belitung Islands Province. The growth rate of Pangkalpinang city is approximately 1.1% per year, with a 29% increase in the number of vehicles being one of the factors contributing to the rise in extreme climate events. This research aimed to examine the trends in extreme air temperatures and extreme rainfall in Pangkalpinang city during the period of 1991-2022. The research method used is secondary data research with a quantitative approach. The study utilized 12 extreme climate indices as defined by ETCCDMI, comprising 7 extreme air temperature indices and 5 extreme rainfall indices. The significant extreme air temperature trend indicates an increase in air temperature in Pangkalpinang, especially the annual average daily maximum temperature of 0.018°C/year, the annual average daily minimum temperature of 0.025°C/year, while the TN10P (Cold night) index experienced a decrease of 0.344°C/year which is the opposite of the TX90p (Warm Days) index trend of 0.273°C/year. The rainfall trend in Pangkalpinang has not changed significantly.